Systematic review on badminton injuries: incidence, characteristics and risk factors - Lars Donath; Oliver Faude; Anne Hecksteden; Brid Stepper; Hendrik Stagge (BMJ Open Sport & Exercise Medicine)
Objectives As a high-intensity intermittent sport with short and repeated rapid accelerations, decelerations and changes of direction, badminton involves high joint and muscle loads. This review aims to identify relevant injury risk characteristics and factors that facilitate developing and implementing badminton-specific injury prevention programmes.Design This systematic review of badminton injuries assessed the risk of bias, injury incidence, mechanism, location, type, severity, and risk factors.Data sources PubMed, WoS, SURF, EBSCO, Ovid and SPORTDiscus.Eligibility criteria Only English or German peer-reviewed articles presenting epidemiological data. All age groups, genders and levels of play were represented.Results Examination of 19 studies with male (60%) and female players (41%) at different player levels (age: 10–50 years). The mean injury incidence was between 1 and 4 injuries/1000 hours, whereby the incidence in the studies that were only carried out with elite players tended to be at the upper end. Lower body injuries occurred most frequently (41%–92%), including strains (11%–64%), sprains (10%–61%), tendinopathy (6%–14%) and stress fractures (5%–11%). There was a high proportion of overuse injuries (25%–74%) and a predominance of mild and moderate injuries (73%–100%). The following risk factors can only be cautiously emphasised due to the heterogeneous results: The risk of injury increases with increasing level of play and a history of injury.Conclusion Young players with a history of injury quickly moving to higher competition classes must be targeted with the highest injury prevention priority. Future studies should focus on improving the quality of studies by using comparable data collection methods.